Parameters of creativity in modern psychotherapeutic practice - Sulyatytskyy, Ivan; Ostrovska, Kateryna; Sajko, Khrystyna; Chorna, Iryna; Khrushch, Olena (Creativity Studies, 2022)
The principal purpose of the study is to determine and compile the main parameters of creativity and creative thinking that affect psychotherapeutic practice. To achieve this goal, the methods of sequencing influence were applied, which allowed offering our methodological approach to the issue of determining the parameters of creativity and creative thinking that are all suitable for the practice of introducing psychotherapeutic activities. Also, the method of expert analysis was used, and by conducting online interviews and polling leading experts in the field of psychotherapy, a list of the most important parameters of creativity that take place in psychotherapeutic practice was determined. As a result, the set goal was achieved, and it was determined which parameter of creativity has the greatest value and influence on psychotherapeutic activity. The study is of practical value since this methodological approach is flexible and can be applied in the practice of a psychotherapist. The study has limitations and they only relate to the psychotherapeutic activity in Ukraine.